A Pathway to First Crystals for Substances Prone to Liquid‐Liquid Phase Separation. Issue 3 (28th January 2021) - Derdour, Lotfi
Abstract: An approach to isolate first crystals for molecules prone to liquid‐liquid phase separation (LLPS) is described. In the absence of knowledge about the solubility of a hypothetical crystal, it is proposed to determine the LLPS phase boundary, then operate at a temperature of 2 °C above the LLPS to maximize the supersaturation with respect to a hypothetical crystalline phase and to avoid LLPS. The proposed approach, combined with a careful solvent and counterion selection based on molecular size, allowed isolating a crystalline salt that was elusive using high‐throughput screening. The crystalline salt displayed higher resistance to mechanical stress than the crystalline parent, allowing the progression of the molecule in the development pipeline. Abstract : The causes of the increasing occurrence of oiling‐out in the pharmaceutical industry are discussed. A pathway to new crystalline solids for substances prone to liquid‐liquid phase separation is proposed. The approach is based on determining the oiling‐out phase boundary, then operating above the oiling‐out temperature. The method is suitable for early development in the pharmaceutical industry.